RICE PRODUCTION AND CONSUMPTION OF FARMER HOUSEHOLDS IN PEKALONGAN REGENCY - Isti Kharoh; Herman Sambodo; Barokatuminalloh Barokatuminalloh (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2023)
Pekalongan Regency is a district with the highest growth rate of the agricultural sector in Central Java, but conventional rice farmers face various problems including fluctuations in rice production, limited resources and farmers who have dual roles as producers and consumers. Further analysis of rice production and consumption among farmer households is needed to address this issue. Therefore, this study aims to examine the factors impacting rice production and consumption, as well as marketable surplus, among farmer households. The research was conducted in Kandangserang District as one of the highest rice producers with a sample of 95 farmers were taken by simple random sampling. The analytical tool used is ordinary least squares. based multiple linear regression. The findings indicate that seed quality, fertilizer use, and the presence of technology significantly impacted rice production, while land area, labor, and technology had no significant effect. Furthermore, the number of family members was a significant factor, while income and rice price had no significant impact to the consumption and the marketable surplus sold was determined to be 46.26%. Based on these results, it is recommended that farmers utilize quality seeds, balanced fertilizers, productive labor, and technology to increase the quantity and quality of rice production. Additionally, the consideration of alternative staple foods to rice may help to increase the marketable surplus available for sale.